Faktor–Faktor Yang Mempengaruhi Keputusan Konsumen Terhadap Pembelian Produk Kerajinan Tangan Dikampung Baru Maroangin Kecamatan Ma’rang Kabupaten Pangkajene Dan Kepulauan - Anugrah Murtini (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
Handicrafts are activities that focus on manual skills and functions to process raw materials that are often found in the environment into objects that are not only of use value but also of aesthetic value. Pangkajene Regency and the islands are areas that are currently under development in tourism in South Sulawesi. This is a market potential for the tourism industry which has an impact on the extent of the local handicraft market. The types of handicraft industry products produced by Pangkep regional craftsmen include bags, shoes, wallets, belts and so on.